Efektifitas Intervensi Self-Management pada Pasien Stroke - Irmina Ika Yuniarti; I Made Kariasa; Agung Waluyo ((JKG) Jurnal Keperawatan Global, 2020)
Background: Stroke is a neurological change that occurs quickly caused by disruption of blood supply to parts of the brain. Stroke has a complex impact which includes bio-psycho-social and spiritual. Various complexities of problems encountered in stroke patients so that self-management is needed as a form of adaptation to new conditions after stroke. Self-management interventions are useful for improving self-management skills and behavior in stroke patients. Purpose this study is to analize effectiveness of self-management interventions in stroke patients. Methods : Narrative literature review, research analyzes published in the online databases of ProQuest, Google scholar and Scopus. The study was selected using the criteria and keywords for the 2015-2019 period. Seven studies were analyzed using the literature review process. Results: To improve self-management stroke patients self-management interventions are needed. Self-management interventions can be applied in hospitals when post acute patients are hospitalized, preparation for discharge, return and after discharge home and can be combined with rehabilitation programs in the community. Self-management interventions can improve self-efficacy, self-management behavior, activity daily living (ADL) ability, decreased re-hospitalisation and patient readiness to return to the community. Conclusion: Self-management interventions can be applied in Indonesia, with a note that among others prepared human resources, costs, supporting facilities and policies from the manager.